A contrastive analysis of the Second Commandment’s translations in early Baltic catechisms - Cerri, Adriano (Baltistica, 2025)
The Second Commandment appears in strikingly varied formulations among Old Prussian, Old Latvian, and Old Lithuanian religious texts, particularly in catechisms from the 16th–17th century. The translation models employed in the three Baltic traditions suggest varying interpretations of the verb expressing the divine prohibition, with meanings including ‘to mention’, ‘to lead’, ‘to take’, ‘to (ab)use’, and ‘to drag, put on’. I seek to explain this remarkable diversity by tracing the attestations back to their immediate and secondary sources.